PENGARUH FINANCIAL TECHNOLOGY TERHADAP PENDAPATAN USAHA KECIL DAN MENENGAH DI DESA LANDUNGSARI KECAMATAN DAU KABUPATEN MALANG - Nurvenia, Nurvenia; Abdullah , Mohammad Faisal (Journal of Financial Economics & Investment, 2021)
This study aims to find out the Effect of Financial Tehnology on Small BusinessIncome. The  type of data used in this study is a type of Primary data that is qualitative and quantitative. Sampling techniques      using  purposive sampling  techniques  with  a total of    50  respondents.   The  data  analysis technique used  is the Multiple Linear  Regression  method.  The results in  this   study  are   partially    Digital Payments positively  and  significantly affect the income  of  small  businesses  in the village of Landungsari  Subdistrict  Dau  Malang,    Financial Management  has a  positive  and  significant effect on the income  of  small  businesses  in  the village  landungsari  Subdistrict Dau  Malang. Then simultaneously, Digital Payments and Financial Management  has  positively and  significantly  affect the income  of  small  businesses  in the village  of Landungsari Subdistrict  Dau Malang.